Truncated Microstrip Patch Antenna with DGS Based on Double Looped CSRR Arrays for Enhancement of Bandwidth - V G Ajay; Thomaskutty Mathew; N.V Krishna Prasad; M.S.S.R.K.N. Sarma (IAES Indonesian Section, 2020)
This paper presents a novel method for the design of truncated microstrip patch antenna with DGS based on Double Looped CSRR arrays for enhancement of bandwidth. The proposed antenna is suitable for WLAN/Wi-Fi, RFID applications. A truncated microstrip patch antenna without DGS was initially designed for a resonant frequency of 2.86GHz having a bandwidth of 95.6MHz. By integrating a new Double Looped CSRR array (DLCSRR) structure on the ground plane, resonant frequency of the antenna is shifted to 2.47GHz and also the bandwidth is enhanced to 202.5MHz. By implementing DLCSRR array structure on the ground plane size reduction and bandwidth enhancement of 52.79% is achieved. The performance of truncated microstrip patch antenna with DGS based on Double Looped CSRR array structure was also compared by replacing conventional proximity fed microstrip patch antenna with the same physical size. The conventional proximity coupled microstrip patch antenna is designed for a resonant frequency of 2.26GHz with a lower bandwidth of 23.3MHz.The antennas were designed using CST simulation software. The measurement result shows a good agreement with simulated results.